Conversion of a New Zealand 30-Metre Telecommunications Antenna into a Radio Telescope. (5th May 2015) - Woodburn, Lewis; Natusch, Tim; Weston, Stuart; Thomasson, Peter; Godwin, Mark; Granet, Christophe; Gulyaev, Sergei
Abstract: The conversion of a former 100-foot (30-m) telecommunications antenna (Earth Station) in New Zealand into a radio telescope is described. A specification of the antenna and the priorities for its actual conversion are initially presented. In describing the actual conversion, particular emphasis is given to mechanical and electrical components, as well as to the design of the telescope control system, telescope networking for VLBI operations, and telescope maintenance. Plans for RF, front- and back-end developments based upon radio astronomical priorities are outlined.